Mastering Qlik Sense : expert techniques on self-service data analytics to create enterprise ready business intelligence solutions /: expert techniques on self-service data analytics to create enterprise ready business intelligence solutions. (2018) - Vitantonio, Juan Ignacio; Mahler, Martin
No abstract available